Mucosal Immunoglobulin IgT at Gilthead Seabream Gill Plays a Predominant Role of Immunity during Vibrio harveyi Infection - Chen Meng-Han; Wang Chung Ping (The Indian Veterinary Journal, 2023)
Teleost gill is considered a mucosal surface and a major site for pathogen entry. This study elucidated the predominant role of IgT, a primitive immunoglobulin classspecialized in mucosal immunity, in the gill of gilthead seabream during V. harveyi infection. Results showed that gill bacteria cells were mainly coated by IgT upon V. harveyi infection. An increase of IgT+ B cells and IgT concentration in gill mucus were also observed. Gilthead seabream devoid of IgT had significant increase of gill bacterial load and became highly susceptible to V. harveyi infection. Taken together, this study demonstrated that IgT plays a predominant role in the antibacterial immunity of gilthead seabream gill.